2016
DOI: 10.1007/s10144-016-0565-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal habitat‐dependent change in nest box occupation by Tengmalm's owl associated with a corresponding change in nest predation

Abstract: We investigated the nest‐site settlement of the forest‐dwelling Tengmalm's owl (Aegolius funereus) in the temperate zone of Central Europe (Czech Republic) over a 14‐year period. We analysed the effect of changes in nest‐site suitability (expressed as the proportion of deciduous forest) within the immediate surroundings of the nest boxes (a buffer radius of 25 m) in relation to nest box occupancy, the mean standardized laying date (further the laying date), occurrence of nest predation, and breeding density. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In particular, young and in- experienced males used to breed in good food years while they do not breed during years of food scarcity (Korpimäki 1988). In our study area, between-year breeding densities of owls do not vary significantly , Zárybnická et al 2015a, Zárybnická et al 2016.…”
Section: Discussionmentioning
confidence: 76%
“…In particular, young and in- experienced males used to breed in good food years while they do not breed during years of food scarcity (Korpimäki 1988). In our study area, between-year breeding densities of owls do not vary significantly , Zárybnická et al 2015a, Zárybnická et al 2016.…”
Section: Discussionmentioning
confidence: 76%
“…The rapid development of molecular technology and theory-based life-history approaches has led to increased research on the reproductive ecology of passerine birds, including life-history characteristics, nest-site selection, reproductive success rate, reproductive countermeasures, and offspring sex ratio, among others [ 7 ]. Zarybnicka et al studied the relationship between nesting box occupation and habitat change in the boreal owl Aegolius funereus and found that the spawning period was positively correlated with the proportion of deciduous leaves around the nesting box [ 8 ]. Libois et al found that using artificial nest boxes effectively increased the survival rate and reproductive success of the mew gull Larus canus [ 9 ].…”
Section: Introductionmentioning
confidence: 99%